HOW CORPORATE GOVERNANCE MODERATES THE LINK BETWEEN EARNINGS MANAGEMENT AND FIRM VALUE - Bangun, Nurainun; Natsir, Khairina (International Journal of Application on Economics and Business, 2025)
This study seeks to empirically analyze the impact of earnings management on firm value and assess the moderating role of corporate governance in this relationship among infrastructure firms listed on the Indonesia Stock Exchange. The research employs a purposive sampling technique, focusing on firms between 2019 and 2023. The data for this research is secondary, sourced from annual reports, company websites, and the Indonesia Stock Exchange. Multiple regression analysis with EVIEWS 9.0 is applied, including classical assumption tests (normality and multicollinearity), as well as model selection tests (Chow, Hausman, and Lagrange Multiplier). Hypothesis testing employs Moderated Regression Analysis and the coefficient of determination test. Findings indicate that earnings management does not significantly influence firm value. Additionally, independent commissioners and institutional ownership fail to moderate this relationship, whereas auditor classification and managerial ownership successfully act as moderators.